220k views
5 votes
Rewrite the function f(x)=4(x-1)^2-2 in the form f(x)=ax^2+bx+c

User Mekka
by
4.5k points

1 Answer

5 votes

Answer:

f(x) = 4x² - 8x + 2

General Formulas and Concepts:

  • Order of Operations: BPEMDAS
  • Expand by FOIL (First Outside Inside Last)
  • Standard Form: f(x) = ax² + bx + c
  • Vertex Form: f(x) = a(bx + c)² + d

Explanation:

Step 1: Define function

Vertex Form: f(x) = 4(x - 1)² - 2

Step 2: Find Standard Form

  1. Expand by FOILing: f(x) = 4(x² - 2x + 1) - 2
  2. Distribute 4: f(x) = 4x² - 8x + 4 - 2
  3. Combine like terms (constants): f(x) = 4x² - 8x + 2
User Joshua Grigonis
by
5.5k points